THE RELATIONSHIP BETWEEN LISTENING STRATEGIES AND STUDENT’S ACHIEVEMENT AT 2nd SEMESTER STUDENTS OF ACCOUNTING PROGRAM POLITEKNIK SEKAYU - Alfha Desiana Maria (Universitas PGRI Palembang, 2018)
Abstract: the aimed of the current study was to describe the relationship between listening strategies and student’s achievement at second semester students of accounting program Politeknik Sekayu. A total population of the research was 160 students. The sample was taken by using convenience sampling which consist of 86 students were involved in this study. Futhermore, there were two variables in this research. The first one was listening strategies (variable X) and the second one was student’s achievement (variable Y). A listening strategy questionnaire was used to identify the strategies they employed in listening was taken from scoring. Based on the data analysis of the listening strategy questionnaire revealed that 2nd semester students of accounting program, it was found that the r-obtained (0.176) was higher than r- table (0.0845). then the level of probability (p) significant relationship (sig.2-tailed) was 0.043. it means that p (0.043) was lower than .05. it meant that null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is rejected. From the reserch finding, it can be concluded that there was significant relationship between the listening strategies and the students’ listening achievement